Fishermen. - Malik, Khirod (Poetcrit)
The poem "Fishermen" by Khirod Malik reflects on the lives of fishermen as they navigate the uncertainties of the sea. The poem captures the daily struggles and hopes of fishermen as they set out to sea, facing the unpredictable nature of their work. Through vivid imagery, the poet portrays the resilience and perseverance of these individuals who rely on the sea for their livelihood.